Turfgrass varietal improvement for shade and drought tolerance using gamma ray irradiation - Baharun Azahar, Mohd Abdul Halim (2014)
Turfgrass breeding aims to improve the characteristics of plants so that they become more desirable agronomically and economically. Alternative methods’ using mutagenic treatment is a relatively quick method for improvement of turfgrass. Gamma ray irradiation can be used to improve turfgrass phenotype and enhance tolerance to environmental stress. A series of experiments were conducted to examine the response of turfgrass species to gamma ray irradiation, either in their phenotypic and genotypic characteristics, and to study turfgrass mutant lines under different shade and drought stress conditions. The mutant lines selected for evaluation in these studies were based on desirable characteristics for performance under stress. Eight gamma ray dosages (0, 20, 40, 60, 80, 100, 150 and 200 Gy) were applied to Axonopus compressus, Zoysia japonica and Cynodon dactylon at the Gamma Cell Laboratory, Malaysian Institute of Nuclear Technology Research (MINT), Bangi, Selangor to identify the optimum dosage for turfgrass mutation. Optimum dosage was needed induce maximum mutation and to increase mutation rate. The optimum dosage was calculated based on 50% radiosensitivity tests on survival rate and plant height. The values 50% of radiosensitivity tests (LD50) were determined to be 52, 76 and 90 Gy for A.compressus, Z.japonica and C. dactylon, respectively. The turfgrasses were radiated using the optimum dosage of gamma ray to produce numerous mutants. A total of 1500 stolons of each species were radiated and planted in biodegradable seed tray. In order to ensure the inheritance of these characteristics, all mutants were isolated using the cutting back technique. Most of the mutants had dwarf and semi-dwarf characters. Gamma ray irradiation significantly altered the morphological parameters of turfgrass. The results showed that 2.4%, 2.6% and 1.5% rate of mutation occurred for A. compressus, Z. japonica and C. dactylon, respectively after exposing to the LD50 dosages. Thirty six lines from A. compressus were recorded as mutants with five (A26-4-1, A61-1-1, A46-2- 1, A91-3-5, A13-2-5) showing high potential for further study. Thirty nine lines from Z. japonica were recorded as mutant with five (Z131-3-1, Z36-3-1, Z13-1-2, Z12-2-1, Z2-2-1) of them showing high potential for further study. Twenty two lines from C. dactylon were recorded as mutants with five (C43-4-1, C85-1-2, C59-2-2, C41-4- 1, C5-3-1) showing high potential for further study, while six (C43-4-1, C42-4-1, C37-5-1, C83-3-2, C95-2-2, C13-3-3) of them were reselected for the shade tolerance study. In the drought tolerance study, six most tolerant mutant lines (A48-3-5, A64-2-2, A62- 3-1, A84-1-1, A26-4-1, A46-2-1) and A0 were subjected to five field capacity treatments of -20, -30, -33 (control), -40 and -50 J/kg and were assessed for visual quality and growth parameters. Shoot and root dry weights were also determined. A. compressus showed low quality performance under extreme drought conditions and many had died. A84-1-1 performed the best under drought conditions as it could withstand up to -50 J/kg field capacity, and this was followed by A26-4-1 and A64-2- 2. In the shade tolerance study treatments were applied by exposing the grass to three, six, nine or twelve hour’s of full sunlight per day. Generally, turfgrass showed slow growth and low quality when exposed to less than 3 hours of sunlight. The quality of C. dactylon was much better under long duration of full sunlight. Mutant line C43-4- 1 performed the best under shade with its outstanding quality in terms of colour, density and uniformity. Durations with a minimum of at least 6 hours sunlight showed good responses.